Multilingual attitudes and attitudes to multilingualism in Croatia - Mihaljević-Djigunović, Jelena (Array, 2013)
The findings in this study indicate that Croatian learners and users of foreign languages have, generally speaking, positve attitudes to foreign language learning and a rather high tolerance for otherness. More open and flexible attitudes are held by females than males, by more educated people, and by people who spent most of their lives in big cities. Positive attitudes are also associated with early foreign language learning, with greater length of learning and with higher self-assessment of foreign language competence. A significant correlation exists between attitudes and the frequency of using foreign languages, especially in private life. Multilinguals and bilinguals have displayed a range of significant differences in attitudes. These differences are evident in attitudes to foreign language learning, in tolerance of otherness, in attitudes to speaking several foreign languages, and in the value that foreign language competence entails. Although many of the relationships we looked into were associated with higher self-perceived competence and frequency of use of the first foreign language, our findings offer important evidence of major attitudinal differences between bilinguals and multilinguals. Therefore, on the basis of our study we would like to suggest that, from the attitudinal perspective, bilinguals and multilinguals should be considered as two separate types of language users.